Wild Actors and Wrathful Deities: Buddhist Faith, Entertainment, and the Kabuki Theatre of Early Modern Japan. (March 2015) - Bond, Kevin
This paper examines the relationship between the celebrated kabuki guild of Ichikawa Danjūrō actors and the popular Narita Fudō deity cult in the capital of Edo in early modern (seventeenth to nineteenth century) Japan. While the actors' worship of the cult and their personifications of the deity on-stage have been well documented by scholarship, less known is how this patronage resulted in the transformation of the deity's character and worship among commoner audiences. By tracing the Danjūrō–Narita Fudō connection among popular media of the day, this paper argues that the guild's artistic incorporation of the deity did not merely represent a religio-commercial collaboration, but the creation of a uniquely contemporary deity specific to Edo's theatrical culture.